Pertanggungjawaban Pidana Korporasi dalam Kasus Korupsi Dana PEN dan Pengadaan Barang atau Jasa (PBJ) di Situbondo - Rindang Gici Oktavianti; Zalfa Dhiaulhaq; Hotimatus Saada (Bhirawa Law Journal, 2026)
This study aims to analyze corporate criminal liability in corruption cases involving the National Economic Recovery (PEN) fund and the procurement of goods/services in Situbondo Regency, as well as to examine the obstacles to its implementation in law enforcement practices in Indonesia. This research employs a normative juridical method using statutory, conceptual, and case approaches. The results indicate that, normatively, corporations have been recognized as subjects of criminal law under the Anti-Corruption Law, and thus can be held liable when criminal acts are committed by their management within the scope of their authority and for the benefit of the corporation. In the context of the Situbondo case, the involvement of private parties in procurement activities demonstrates the potential for corporate criminal liability. However, in practice, law enforcement still tends to focus more on punishing individuals, while corporations as legal entities have not been held fully accountable. This is due to several obstacles, including difficulties in proving the element of corporate fault, the complexity of organizational structures, and the limited capacity of law enforcement officials. In addition, weak internal control and compliance systems within corporations further increase the likelihood of corruption. Therefore, it is necessary to strengthen regulations, enhance the capacity of law enforcement officials, and implement effective corporate compliance systems to ensure that corporate criminal liability can be applied optimally and provide a deterrent effect in combating corruption.